EFEKTIFITAS TERAPI MENGANYAM TERHADAP FUNGSI KOGNITIF PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA SINTA RANGKANG PALANGKA RAYA - Saputra, Teguh; Carolina, Meilitha; Araya, Wenna; Adelheid Ensia, Maria (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
Weaving therapy is an activity carried out by the elderly, because weaving therapy is able to improve the quality of cognitive function in the elderly who have experienced a decline in cognitive function. Weaving is a skill activity that has the aim of producing objects or in the form of goods and art that is carried out by hitchhiking overlap the parts of woven material alternately, it has a good function in improving cognitive function in the elderly who experience such a decrease in cognitive function, significantly that the decline in cognitive function is related to memory impairment, perceptual changes, problems in communication, decreased focus, attention and obstacles in the improvement of on the quality of life of an elderly person. This study aims to determine the effectiveness of weaving therapy on cognitive function in the elderly at the Tresna Werdha Sinta Rangkang Palangka Raya Social Institution. The research design uses a pre-experimental design research design with a one-group pretest and posttest design approach, to see the effectiveness of weaving therapy on improving cognitive function in the elderly. The population in this study was the elderly who were in the Tresna Werdha Sinta Rangkang Palangka Raya Social Institution as many as 12 respondents consisting of an experimental group with poor cognitive function. Based on statistical test analysis with Wilcoxon test obtained p value = Value (Asymp. Sig. (2- tailed)) with a p value (p value) of 0.003, because the value of 0.003 is smaller than <0.05, it can be concluded that H1 is accepted which means that the results of the Wilcoxon test show the effectiveness of weaving therapy on cognitive function in the elderly. From this study it can be concluded that there is an effectiveness of weaving therapy on cognitive function in the elderly. With this research, it is hoped that it can add new things to complementary therapies through preventive and promotive efforts to apply weaving therapy regularly.